Pro Windows PowerShell - Deshev, Hristo (Apress : Imprint: Apress, 2008)
Windows power users have always envied their friends running UNIX machines for the ease of automation that they enjoy. The traditional Windows command-line shell, cmd.exe, has never been up to par with shells like bash or tcsh, especially when it comes to text processing and process automation. Windows PowerShell changes all that. This next-generation shell is also a full-blown scripting environment with a real programming language that allows users to access every part of their operating system. Files, registry entries, and COM and .NET objects are all supported by PowerShell, which makes manipulating them a breeze. Pro Windows PowerShell will show you how to use all this power in your own work. You'll discover the object-oriented features of the shell and how they help in extracting and manipulating data. You'll then learn how to use those features to solve real-world problems: manipulating files, working with text, monitoring systems, and performing operations over the network. The book serves as not only a tutorial, but also a reference: the "Real World" part is structured so that it can be read nonlinearly and used as a reference or a cookbook. And you'll find freely available tools and extensions that will help you do things even faster. Pro Windows PowerShell is your best companion to the capabilities and power that PowerShell offers you. .